PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII MTsN LUBUK BUAYA PADANG - Yulianti Rasyid, Fadhlan Lazuardi, Erizal Gani, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
There are three purpose of this study. First, it aimed to know the level of skill in writing observation report (LHO) before using (PBL) helped by the use of audiovisual. Second, knowing the level of skill in writing LHO by using PBL helped by the use of audiovisual . Third, this study describing the effect of using PBL helped by audiovisual to skill of writing LHO. This sudy is a kuantitatif research with quasi-experiment methode. It can concluded that the skill of writing LHO after using PBL helped by audiovisual is more good use rather than the skill of wrting LHO before using PBL helped by audiovisual.Â Kata kunci: pengaruh,Â  model Problem Based Learning, teks laporan hasil observasi